Life and work of Abu Nasir Mubashir at-Tarazi in Afghanistan (Journal of Oriental Studies, 2021)
The article analyzes the social and political activities of a native of Taraz and theologian Abu Nasir Mubashir at-Tarazi (1896-1977) during 1930-1949, who emigrated to Afghanistan during the Soviet era because he struggled against the communist regime. Authors provide information about the scientist's activities in translation and editing, management, administration, printing, and literary and creative work in the Shah's office, about his active social struggle. The article reports that he led the preparation of a joint German armed operation by Turkestan emigrants against the Soviet Union, which is why he was arrested and imprisoned in Kabul for five years, one month, and three days. There also explained the reason for his emigration to Egypt after his release from prison. The article provides data that can be applied to study the history of the East, the national liberation movement, and the history of Islam.The article uses new materials in Arabic that were not previously included in the scientist's fund in the Central State Archives of the Republic of Kazakhstan, as well as the works of his son Nasrullah at-Tarazi (1922-2002). Arab sources were collated and supplemented by the memoirs of Abdulhamid Kochar in Turkish, research by Ahad Andijan and Amin Yarimoglu, data from books based on intelligence materials in Russian. In the study, the authors used the principles of characterization, systematization, historical and cognitive methods, and method of generalization.Mubashir аt-Tarazi is considered a public figure in Afghanistan, an influential figure in the movement for independence and liberation. Therefore, it is significant to study his biography, personal and creative path and provide the reader with the missing information.